2020
DOI: 10.1093/geront/gnaa140
|View full text |Cite
|
Sign up to set email alerts
|

Helping Amid the Pandemic: Daily Affective and Social Implications of COVID-19-Related Prosocial Activities

Abstract: Background and Objectives The novel coronavirus disease 2019 (COVID-19) pandemic may have prompted more engagement in prosocial activities, such as volunteering and support transactions. The day-to-day affective and social implications of these activities for adults of different ages are unknown. The current study examined associations of daily prosocial activities with affective and social well-being, and whether these associations varied by age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 31 publications
10
52
0
1
Order By: Relevance
“…Networks that were developed within social organizations likely eased depression and maintained their subjective memory. This is consistent with findings that older ages were more likely to provide and receive support during COVID-19, which were associated with better mental health [ 38 ]. Social organizations may be the primary sources of this mutual support during COVID-19.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Networks that were developed within social organizations likely eased depression and maintained their subjective memory. This is consistent with findings that older ages were more likely to provide and receive support during COVID-19, which were associated with better mental health [ 38 ]. Social organizations may be the primary sources of this mutual support during COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…These weak relationships are insufficient to overcome mental health challenges in the event of a pandemic. They may be “too little, too late.” More robust community development work is required to ensure that these older adults are included in “natural neighborhood networks” for their well-being [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 1 study of adults living in Canada and the U.S, older age predicted more support provision and receipt due to COVID-19; however this was primarily related to emotional support rather than tangible support. 22 Our results underscore the resiliency and creativity that many older individuals have demonstrated during this crisis, and suggests they were able to identify ways to maintain connections and continue to receive any necessary assistance.…”
Section: Discussionsupporting
confidence: 53%
“…Harvey and Erdos note that the psychological factors of risk-assisted behavior in an emergency area are altruism, heroism, and prosocial orientation of the individual (Harvey and Erdos, 2003 ). Studies conducted in Spain (Serrano-Montilla et al, 2021 ), Serbia (Dinić and BodroŽa, 2021 ), Canada, and the United States (Sin et al, 2021 ) showed that the health threat of COVID-19 predicted a tendency to express altruistic prosocial actions: anonymous helping behavior (Dinić and BodroŽa, 2021 ), volunteering and providing support (Sin et al, 2021 ), empathic care (Serrano-Montilla et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%